Pyrroloquinoline quinone against glutamate-induced neurotoxicity in cultured neural stem and progenitor cells. Issue 42 (May 2015) - Guan, Shui; Xu, Jianqiang; Guo, Yifu; Ge, Dan; Liu, Tianqing; Ma, Xuehu; Cui, Zhanfeng
Highlights: PQQ stimulates cell proliferation and attenuates glutamate-induced NS/PCs damage. PQQ pretreatment protects NS/PCs against glutamate-induced apoptosis/necrosis. PQQ decreases ROS production and increases GSH content exposed to glutamate. PQQ pretreatment enhances intracellular SOD, CAT and GPx activities. PQQ neuroprotection is associated with ROS-mediated mitochondrial pathway. Abstract: Pyrroloquinoline quinone (PQQ), as a well-known redox enzyme cofactor, has been proven to play important roles in the regulation of cellular growth and development in mammals. Numerous physiological and medicinal functions of PQQ have so far been reported although its effect on neural stem and progenitor cells (NS/PCs) and the potential mechanism were even rarely investigated. In this study, the neuroprotective effects of PQQ were observed by pretreatment of NS/PCs with PQQ before glutamate injury, and the possible mechanisms were examined. PQQ stimulated cell proliferation and markedly attenuated glutamate-induced cell damage in a dose-dependent manner. By observing the nuclear morphological changes and flow cytometric analysis, PQQ pretreatment showed its significant effect on protecting NS/PCs against glutamate-induced apoptosis/necrosis. PQQ neuroprotection was associated with the decrease of intracellular reactive oxygen species (ROS) production, the increase of glutathione (GSH) levels, and the decrease of caspase-3 activity. In addition, pretreatment with PQQ also significantly enhanced the activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) in the NS/PCs exposed to glutamate. These results suggest that PQQ can protect NS/PCs against glutamate toxicity associated with ROS-mediated mitochondrial pathway, indicating a useful chemical for the clinical application of NS/PCs.